STANDARDS FOR THE PHARMACY CUSTOMER SERVICE: OPINIONS OF DIRECTORS AND PHARMACEUTICAL PERSONNEL - O. A. Kulikova; L. I. Lavrentyeva (Фармация и фармакология (Пятигорск))
Nowadays pharmacy organizations are actively introducing customer service standards into their activity. Efficiency of their introduction depends from the whole range of factors including the recognition of their significance and necessity by every expert. The purpose of the study is to compare the opinions of directors and pharmaceutical personnel about the use of pharmacy organizations activity standards of customer service. 50 directors and 50 pharmacy organization workers participated in the questionnaire. The study included the revelation of respondents’ attitude towards the service standards, estimation of their positive and negative sides, analysis of the necessary requirements and standards structure, revelation of the most hard- and easy-to-use sections of service standards. We have established that both categories of respondents noted a big number of positive sides of work following standards, including the influence on the goods turnover, service quality, and customer attraction. But some directors and personnel members were negative or neutral about the service standards. We have revealed that the implementation of standard sections about communication with a customer by the phone and conflict situations resolution were the biggest problem for the personnel. There are differences in opinions of directors and pharmaceutical personnel about the necessary structure and content of customer service standards in pharmacy organizations. The results obtained should be used for the management functions realization regarding the service standards.